2017
DOI: 10.1111/jpn.12796
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hepatic glucose and lipid metabolism‐related parameters in domestic pigeon (Columba livia) during incubation and chick rearing

Abstract: This study aimed to evaluate the hepatic glucose and lipid metabolism-related parameters of adult male and female White King pigeons (Columba livia) during incubation and chick rearing. At day 4 (I4), 10 (I10) and 17 (I17) of incubation and day 1 (R1), 7 (R7), 15 (R15) and 25 (R25) of chick rearing, livers were sampled from six pigeons for each sex. Glycogen and fat contents, activities of glycolytic enzymes (hexokinase, HK; 6-phosphofructokinase, 6-PFK), and genes expressions of key enzymes involved in glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…AMPK α and its downstream metabolic enzyme ACC have been identified as potential targets for the treatment of metabolic disorder, due to their inhibitory effects on glucose and lipid metabolism . Activation of AMPK/ACC pathway can enhance glucose uptake and glycolysis, while inhibit lipogenesis and cholesterol biosynthesis in the liver . Besides, G6Pase , FBPase and PEPCK genes are responsible for gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK α and its downstream metabolic enzyme ACC have been identified as potential targets for the treatment of metabolic disorder, due to their inhibitory effects on glucose and lipid metabolism . Activation of AMPK/ACC pathway can enhance glucose uptake and glycolysis, while inhibit lipogenesis and cholesterol biosynthesis in the liver . Besides, G6Pase , FBPase and PEPCK genes are responsible for gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…50 Activation of AMPK/ACC pathway can enhance glucose uptake and glycolysis, while inhibit lipogenesis and cholesterol biosynthesis in the liver. [51][52][53] Besides, G6Pase, FBPase and PEPCK genes are responsible for gluconeogenesis. It has been well established that the downregulation of G6Pase, FBPase and PEPCK genes can significantly inhibit gluconeogenesis, and subsequent reduce blood glucose levels.…”
Section: Further In Vivo Experiments Revealed That Bmh473 Significantlymentioning
confidence: 99%
“…Our results showed that pancreatic amylase activity gradually decreased from I4 to R1 but then recovered to the beginning level in the late chick-rearing period. Pigeon serum glucose concentration was stable from egg incubation to chick rearing ( Xie et al., 2018 ), but hepatic glycogen content was reported to decrease significantly during the incubation period and then recovered when feeding nestlings ( Wan et al., 2018 ). In addition, our present study indicated that the activities of maltase and sucrose in mucosa also maintained a relatively lower level from I17 to R1.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have focused on the organ and metabolic changes in breeding birds, except during the migration and molting processes ( Christians and Williams, 1999 , Landys-Ciannelli et al., 2003 , Vézina and Williams, 2003 ). In our previous study, the body and organs of parental pigeons, shown to be a nutrient reserve, fluctuated in weight during incubation and chick-rearing period, and serum biochemical profiles and enzyme expression in the liver of breeding pigeons also changed significantly ( Wan et al., 2018 ; Xie et al., 2018 ). Dietary intake of parent pigeons was found to increase significantly when feeding squabs ( Xie et al., 2016 ); therefore, will the pigeon intestine vary in its morphology or digestive and absorption function, similar to mammals, for dealing with these changes?…”
Section: Introductionmentioning
confidence: 89%
“…Glycolysis and gluconeogenesis serve important roles in supplying ATP for hypoxic metabolism, cellular proliferation and apoptosis ( 41 ). Several enzymes and proteins, including hexokinase-2, aldolase A and glucose-6-phosphate isomerase, associated with glycolysis and gluconeogenesis may be potential molecular targets in pancreatic, breast and gastrointestinal tumors ( 42 , 43 ). The ribosome signaling pathway has been implicated in a wide variety of biological functions, including cell cycle progression, apoptosis and DNA damage responses ( 44 47 ).…”
Section: Discussionmentioning
confidence: 99%